Genetic parameters estimated in different types of experimental plots in soybean (Glycinne max (L.) Merrill) - Mauro, Antonio Orlando; Sedyiama, Tuneo; Sedyiama, Carlos Sigueyuki (Pesquisa Agropecuaria Brasileira, 1995)
Four types of experimental plots as follows: conventional lines, hills and mixture of equal amount of seeds of the genotypes Paraná, Santa Rosa, IAC-2, Bossier, Doko, UFV-1, UFV-2, UFV-4, UFV-5 e Sucupira, which were employed in this study, were evaluated considering the correlation coefficient, heritability and genetic gain. The characters plant height, first pod insertion, number of pods per plant, number of seeds per pod, weight of one hundred seeds and yield were measured. For estimating the genetic gain, a selection index of 30% of the best genotypes was considered. The results showed that higher values for the two parameters were observed in the hill plots. On the other hand, lower values were detected in the genotypic mixture. Some equality among the values obtained in the conventional plots and in the lines was observed, suggesting that, based on this two parameters and also on the correlations, lines can substitute the conventional plots when there are limitations of seeds, room, time and labour.